Human resource management adaptation among family firms operating in Western Australia: An exploratory study - O'Shea, Michelle; Duarte Alonso, Abel (Emerald, 2020)
Purpose – The purpose of this study is to draw on the experiences of family owned firms, and explore how contemporary human resource management and allied developments shape their business practices. Design/methodology/approach – Interviews were conducted with eight family businesses involved in several industries in Western Australia. Findings – Significant strengths emerged relevant to ‘formalised HRM processes’ and ‘familiness’. However, challenges were simultaneously experienced or interpreted as negatively affecting family firm performance. In addition, there was a relationship between challenges and external environmental factors. These challenges are categorised as ‘labour costs and supply’ and ‘formalising HRM practices’. Further, participants discussed emerging opportunities, and how they were strategically considering the relationship between organisation finance, innovation, future growth, operations, and HRM. Originality/value – From a practical standpoint, the research addresses the complexities of managing contemporary human resource management developments in ways that contribute to improved family firm performance. From a theoretical perspective, key insights of the resource-based view of the firm and strategic human resource management theory are considered to gain a deeper understanding of family firms’ adaptive managerial activities.